2006
DOI: 10.2337/dc05-1973
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in HbA1c Levels Between African-American and Non-Hispanic White Adults With Diabetes

Abstract: OBJECTIVE—Among individuals with diabetes, a comparison of HbA1c (A1C) levels between African Americans and non-Hispanic whites was evaluated. Data sources included PubMed, Web of Science, the Cumulative Index to Nursing and Allied Health, the Cochrane Library, the Combined Health Information Database, and the Education Resources Information Center. RESEARCH DESIGN AND METHODS—We executed a search for articles published between 1993 and 2005. Data on sample size, age, sex, A1C, geographical loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
224
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 308 publications
(240 citation statements)
references
References 44 publications
13
224
1
2
Order By: Relevance
“…Black patients with diabetes are less likely than white patients to receive appropriate hemoglobin A1c and lipid testing 1,2 and less likely to achieve treatment goals including glycemic, cholesterol, and blood pressure control. [3][4][5][6][7][8] Blacks also experience worse long-term diabetes-related outcomes than whites, including diabetic retinopathy, 9 lower extremity amputations, 2,10,11 and chronic kidney disease. 12 Hispanics and Native Americans have also been found to receive lower-quality diabetes care, with Native Americans experiencing disproportionately high rates of lower extremity amputations, chronic kidney disease, and diabetes-related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Black patients with diabetes are less likely than white patients to receive appropriate hemoglobin A1c and lipid testing 1,2 and less likely to achieve treatment goals including glycemic, cholesterol, and blood pressure control. [3][4][5][6][7][8] Blacks also experience worse long-term diabetes-related outcomes than whites, including diabetic retinopathy, 9 lower extremity amputations, 2,10,11 and chronic kidney disease. 12 Hispanics and Native Americans have also been found to receive lower-quality diabetes care, with Native Americans experiencing disproportionately high rates of lower extremity amputations, chronic kidney disease, and diabetes-related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…the higher prevalence of chronic complications of DM and worse evolution of DN and DR in this population. Recently, in a meta-analysis performed in American patients with type 2 DM, patients of African ethnicity had worse metabolic control than whites 23 . Black patients presented a mean A1c 0.65% higher than whites 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a meta-analysis performed in American patients with type 2 DM, patients of African ethnicity had worse metabolic control than whites 23 . Black patients presented a mean A1c 0.65% higher than whites 23 . Data on the Brazilian population are scarce and, in the present sample, the glycemic control was similar among the ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Furthermore, suboptimal control is often more prevalent among African Americans. 1,2,[8][9][10][11][12][13][14][15][16][17][18][19][20] Prior research has consistently found racial differences in medication adherence. [21][22][23][24] The reasons underlying such differences are poorly understood, but are often thought to stem from differences in care access, care quality, and selfmanagement behaviors.…”
Section: Introductionmentioning
confidence: 99%